On the Use of Information in Repeated Insurance Markets - Iris Kesternich; Heiner Schumacher (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We analyze the use of information in a repeated oligopolistic insurance market. To sustain collusion, insurance companies might refrain from changing their pricing schedules even if new information about risks becomes available. We therefore provide an explanation for the existence of unused observables that is information which
urn:nbn:de:bvb:19-epub-13274-1
Keywords: G22; L13; 330; repeated games; insurance markets; oligopoly; unused observables